IDENTIFY THE RISKS OF HONEY PRODUCTION IN CV. HONEY APIARI MUTIARA DEPOK- WEST JAVA - Iwan Aminudin; Elpawati Elpawati; Fauziyah Rahmah (AGRIBUSINESS JOURNAL, 2022)
Madu Apiari is pure honey that has been specific, depending on where the bees are grazed. The distribution is always supervised by IPB LPPM, IPB Bee Experts, and the Head of the Pest or Forest Entomology Laboratory, Faculty of Forestry, Bogor Agricultural University. In carrying out its business, the company risks any honey production process. This study aims to identify, measure, and map priorities, and risk mitigation strategies. In data research using observation and interview methods as well as data analysis methods used in experimental work, in this case, are Fishbone Diagrams, House of Risk (HOR) stage 1, Pareto Diagrams, and House of Risk (HOR) stage 2. The results of the study are known to be in the honey production process in CV. Madu Apiari Mutiara, there are 15 risk events or Risk Events (Ei). Then based on the mapping, 17 risks are priority risks. In terms of the causes of risk priority, 10 risk mitigation strategies will be determined.